NHCs Catalyzed Hydrophosphonylation of α-Ketoesters and α-Trifluoromethyl Ketones. (31st December 2013) - He, Lin; Cai, Zhi-Hua; Pian, Ji-Xin; Du, Guang-Fen
Abstract : N-Heterocyclic carbenes catalyzed hydrophosphonylation reaction of α -ketoesters and α -trifluoromethyl ketones was developed. Under the catalysis of 10 mol% IPr, α -ketoesters or α -trifluoromethyl ketones reacted with dialkyl phosphites to provide quaternary α -hydroxyphosphonates in good to excellent yield.